1360 REVIEW OF OUTCOMES OF PATIENTS ADMITTED TO AN ENHANCED ASSESSMENT BED AT AN INTERMEDIATE CARE UNIT. (16th January 2023) - Mason, C; Edwards, S; Packer, S; Mahmood, K; Gupta, A
Abstract: Introduction: The Norman Power Centre (NPC) is an Intermediate Care Unit, in Birmingham, UK, providing enhanced assessment beds (EAB) where patients undergo functional assessment after an acute admission. There is little published data regarding the outcomes for patients admitted to EAB, so we set out to analyse outcomes in our unit. Method: Data was collected from 50 patients who were discharged from EAB between September 2021 and March 2022. Results: The mean length of stay was 36 days, median was 29 days. Of the 50 patients: 4 went home with no services, 9 went home with Early Intervention Community Team (EICT) support, 5 went home with package of care (not EICT), 13 went to new residential home placements, 6 went to new nursing home placements, 11 were re-admitted to hospital, 1 died and 1 received palliative care. 28 patients went to the destination that was originally intended on admission, 9 went to a less restrictive option and 12 required a higher dependency destination (predominantly re-admission to hospital.) The change in Elderly Mobility Scale from admission to discharge ranged from -1 to +15. Mode and median were both 0 and mean change was +2. 49 patients had Barthel scores on admission and discharge. Change in score ranged between -1 and +9. Mode and median change was 0, and mean was +1.7. Conclusions: This data shows positive outcomes in terms of discharging most patients to their intended, or better, destinations. It also gives us an objective measure of the change in functional status that patients are achieving during their stay. There is a high rate of hospital re-admissions, indicating the unstable nature of the health of frail people. We are now ready to move onto a PDSA cycle to see if we can improve outcomes for our patients.